Review and Content Analysis of the International Review of Research in Open and Distance/Distributed Learning (2000–2015) - Zawacki-Richter, Olaf; Alturki, Uthman; Aldraiweesh, Ahmed (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This paper presents a review of distance education literature published in the International Review of Research in Open and Distance/Distributed Learning (IRRODL) to describe the status thereof and to identify gaps and priority areas in distance education research based on a validated classification of research areas. All articles (N = 580) published between 2000 and 2015 were reviewed for this study. An analysis of abstracts using the text-mining tool Leximancer over three 5-year periods reveals the following broad themes over the three periods: the establishment of online learning and distance education institutions (2000–2005), widening access to education and online learning support (2006–2010), and the emergence of Massive Open Online Courses (MOOCs) and Open Educational Resources (OER) (2011–2015). The analysis auf publication and authorship patterns revealed that IRRODL is a very international journal with a high impact in terms of citations.